Exploring some of Cicely Berry’s voice and language exercises for a directing concept of Athol Fugard’s Sorrows and Rejoicings - Hofmeyr, Zoettje (Stellenbosch : Stellenbosch University, 2016)
Thesis (MDram)--Stellenbosch University, 2016.